PENGARUH MANAJEMEN HUBUNGAN MASYARAKAT DAN ORIENTASI PEMASARAN HUBUNGAN TERHADAP LOYALITAS MEREK DENGAN KETERLIBATAN PELANGGAN DAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI [THE INFLUENCE OF PUBLIC RELATIONS MANAGEMENT AND RELATIONSHIP MARKETING ORIENTATION ON BRAND LOYALTY WITH CUSTOMER INVOLVEMENT AND BRAND TRUST AS MEDIATION VARIABLES] - Andrean Steviano; Sabrina Oktaria Sihombing (DeReMa (Development Research of Management): Jurnal Manajemen, 2023)
The development of the food and beverage industry, especially the cafe business, is classified as fast growing. Cafes are a type of business that is rapidly growing along with changes in people's lifestyles. Cafes are not only a place to enjoy food and drinks, but a place for mixing cultures and subcultures for social communities which are places to socialize. This research was conducted to determine the effect of public relations management and relationship marketing orientation on brand loyalty with customer involvement and brand trust as mediating variables. This study uses quantitative methods and data collection techniques by distributing electronic questionnaires using non-probability sampling methods, namely purposive sampling. The samples taken for this study were 188 respondents. Data were analyzed using Structured Equation Modeling-Partial Least Squares (PLS-SEM) with SmartPLS3 software. In this study there are ten hypotheses and supported and four unsupported hypotheses. The results of this study indicate that there is a positive influence between community relationship management and customer engagement and brand trust. There is a positive influence between relationship marketing orientation and customer engagement and brand loyalty. There is a positive influence between customer engagement with brand trust and brand loyalty. There is a positive influence between brand trust and brand loyalty. There is a positive influence between relationship marketing orientation and brand loyalty mediated by customer engagement. There is a positive influence between relationship marketing orientation and brand loyalty mediated by brand trust. There is a positive influence between customer engagement and brand loyalty mediated by brand trust. Then, there is no positive influence between community relationship management and brand loyalty. There is no positive influence between relationship marketing orientation and brand trust. There is no positive influence between community relationship management and brand loyalty mediated by customer engagement. There is no positive influence between community relationship management and brand loyalty mediated by brand trust. This study provides theoretical implications, managerial implications, and recommendations for further research.Abstrak dalam Bahasa Indonesia. Kafe merupakan salah satu jenis usaha yang cepat bertumbuh seiring dengan perubahan gaya hidup masyarakat. Kafe tidak hanya menjadi tempat untuk menikmati makanan dan minuman, namun menjadi tempat percampuran budaya dan subkultur bagi komunitas sosial yang menjadi tempat untuk bersosialisasi. Penelitian ini dilaksanakan untuk mengetahui pengaruh manajemen hubungan masyarakat dan orientasi pemasaran hubungan terhadap loyalitas merek dengan keterlibatan pelanggan dan kepercayaan merek sebagai mediator. Penelitian ini menggunakan metode kuantitatif dan teknik pengumpulan data menggunakan Google form dengan menggunakan metode sampling non probabilitas yaitu, sampling bertujuan. Sampel yang diambil untuk penelitian ini adalah 188 responden. Data dianalisis menggunakan Structured Equation Modelling- Partial Least Square (PLS-SEM). Hasil penelitian ini menunjukkan bahwa terdapat pengaruh positif manajemen hubungan masyarakat dengan keterlibatan pelanggan, dan kepercayaan merek. Terdapat pengaruh positif orientasi pemasaran hubungan dengan keterlibatan pelanggan dan loyalitas merek. Terdapat pengaruh positif keterlibatan pelanggan dengan kepercayaan merek dan loyalitas merek. Terdapat pengaruh positif kepercayaan merek dengan loyalitas merek. Terdapat pengaruh positif orientasi pemasaran hubungan dengan loyalitas merek yang di mediasi oleh keterlibatan pelanggan. Terdapat pengaruh positif orientasi pemasaran hubungan dengan loyalitas merek yang di mediasi oleh kepercayaan merek. Terdapat pengaruh positif keterlibatan pelanggan dengan loyalitas merek yang di mediasi oleh kepercayaan merek. Kemudian tidak terdapat pengaruh positif manajemen hubungan masyarakat dengan loyalitas merek. Tidak terdapat pengaruh positif orientasi pemasaran hubungan dengan kepercayaan merek. Tidak terdapat pengaruh positif manajemen hubungan masyarakat dengan loyalitas merek yang di mediasi oleh keterlibatan pelanggan. Tidak terdapat pengaruh positif manajemen hubungan masyarakat dengan loyalitas merek yang di mediasi oleh kepercayaan merek.